Because UI and EI rules "works" only with outermost quantifiers, i.e. when we have e.g. (∃x)Px.
If we have instead (∃x)Px ⊃ (∃y)Qy, we cannot apply the quantifier rules to remove them.
According to your question 2, you think that the proof should be 'simpler' as follows :
[1A] i.e. 11) (∃x)(∃y)(Jxy ∨ Kxy) --- premise
[1C] i.e. 12) (∃x)Lx --- premise
2) (x)(y)(Lx ⊃ ¬Ly) --- premise
13) Lo --- from 12) by EI
14)-15) Lo ⊃ ¬Lo --- from 2) by UI twice
16) ¬Lo --- from 13) and 15) by MP
17) Lo ∧ ¬Lo --- from 13) and 16) by Conj
Now we have a contradiction and thus - according to the IP rule - we have to "discharge" one of the premises to derive this one premise's negation. We may discharge 12), deriving :
The derivation is formally correct, but what we have proved is:
from the premises : (∃x)(∃y)(Jxy ∨ Kxy), (∃x)Lx, (x)(y)(Lx ⊃ ¬Ly),
it follows ¬(∃x)Lx.
Please, note that the derivation does not use [1A] at all; thus (as we can imagine) the derivation boils down to :
(x)(y)(Lx ⊃ ¬Ly) implies ¬(∃x)Lx.
The textbook's original proof was instead :
from the premises : (∃x)(∃y)(Jxy ∨ Kxy) ⊃ (∃x)Lx, (x)(y)(Lx ⊃ ¬Ly),
it follows (x)(y)¬Jxy,
which is quite different.